Customer Satisfaction Strategy Through Improving The Quality Of Services And Quality Products - Windarti Windarti; Anggalia Wibasuri (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to comprehend and analyze customer satisfaction strategies by improving service quality and product quality at warungtetanggamu.com. The method of this study used qualitative research methods. The analysis method used the EFAS and IFAS matrix SWOT analysis method. The data analysis used external factors and internal factors in warungtetanggamu.com included strengths, weaknesses, opportunities, and threats. The methods of data collection were carried out by field research/field research. The data collection was carried out in natural conditions (natural setting) to produce data that actually occurs in the field. The result of the EFAS and IFAS SWOT matrix analysis showed that warungtetanggamu.com was on a strategic path, namely in quadrant I (+, +) with warung tetanggamu.com was an online shop that is in a very profitable position.Keywords : Strategy, Customer Satisfaction, Service Quality, Product Quality